(untitled) (Scottish Historical and Archaeological Internet Reports, 2004)
During the initial inspection of the vein, it soon became clear that it had been exploited by prehistoric people. The main revealing attributes are ’stepping’, circular impact scars, and denticulated ’platform-edges’. These features and others are described and illustrated in detail.